2016
DOI: 10.1039/c5dt01541c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of bis(imino)pyridine complexes of divalent Mg and Zn

Abstract: Phenyl-bis(imino)pyridine (PhI2P) complexes, (PhI2P)ZnCl2 (1), (PhI2P−)ZnCl (2) and (PhI2P−)Zn(py)Cl (3) were obtained with the I2P ligand in both the neutral and the one-electron reduced state. In all examples, the metal ion is Zn(II). Metrical parameters obtained from solid state structures of 2 and 3 indicate that the PhI2P− ligand exists as a radical which is supported at the carbon atom of the imino donor, and this electronic state is also apparent in the analogous one-electron reduced ligand Al(III) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 40 publications
4
26
0
Order By: Relevance
“…[12] We now focus on ligand reactivity only,and report herein that the analogous aluminum chloride complex [( Ph I 2 P 2À )Al-(THF)Cl] (1,S cheme 2) [13] promotes H 2 production from protons in the presence of an applied reducing potential. We also discuss [( Ph I 2 P 1À )AlCl 2 ]( 2), [14] where the After addition of two equivalents of 2,6-lutidinium acid (lutH + )t oasolution of 1,t wo reduction events were observed, namely at À0.95 Va nd À1.20 V, and the anodic shift of these events compared with reduction of 1 (À1.55 V) is consistent with the additional positive charge on the complex resulting from protonation of the ligand (Figure 1a). With excess lutH + ,the current density increased to j c /j p = 10; this result suggested that ac atalytic event had occurred ( Figure 2a).…”
Section: Akeyareaofresearchintofuel-producingelectrocatalystsismentioning
confidence: 99%
See 2 more Smart Citations
“…[12] We now focus on ligand reactivity only,and report herein that the analogous aluminum chloride complex [( Ph I 2 P 2À )Al-(THF)Cl] (1,S cheme 2) [13] promotes H 2 production from protons in the presence of an applied reducing potential. We also discuss [( Ph I 2 P 1À )AlCl 2 ]( 2), [14] where the After addition of two equivalents of 2,6-lutidinium acid (lutH + )t oasolution of 1,t wo reduction events were observed, namely at À0.95 Va nd À1.20 V, and the anodic shift of these events compared with reduction of 1 (À1.55 V) is consistent with the additional positive charge on the complex resulting from protonation of the ligand (Figure 1a). With excess lutH + ,the current density increased to j c /j p = 10; this result suggested that ac atalytic event had occurred ( Figure 2a).…”
Section: Akeyareaofresearchintofuel-producingelectrocatalystsismentioning
confidence: 99%
“…[12] We now focus on ligand reactivity only,and report herein that the analogous aluminum chloride complex [( Ph I 2 P 2À )Al-(THF)Cl] (1,S cheme 2) [13] promotes H 2 production from protons in the presence of an applied reducing potential. We also discuss [( Ph I 2 P 1À )AlCl 2 ]( 2), [14] where the Ph I 2 Pl igand is reduced by only one electron.…”
Section: Akeyareaofresearchintofuel-producingelectrocatalystsismentioning
confidence: 99%
See 1 more Smart Citation
“…Redox activity of mononuclear Zn(II) complexes in redox-active environments has been investigated, [13,14] including recent electrochemical characterization of bis(imino)pyridine Zn(II) complexes and isolation of the reduced bis(imino)pyridine Zn(II) complexes by Berben and coworkers. [15] We wanted to find out whether our complexes, featuring two bis(imino)pyridine units bridged by a [Zn 2 (oxalate)] bridge, also demonstrate reduction events associated with redox-active ligands. Second, we were interested in discovering whether oxalate can be removed from our complexes via oxidation.…”
Section: Electrochemical Characterization Of Compounds 1-3mentioning
confidence: 99%
“…The electrochemical features observed in the cyclic voltammogram are assigned to the redox-active nature of the bis(ketimino)pyridine ligands bound to the redox-inactive zinc. [15] Interestingly, Berben and coworkers have also observed two redox events at the mononuclear bis(imino)pyridine zinc complex with the first event being irreversible due to chloride loss. In our case, the first event is reversible, likely due to the rigid…”
Section: Electrochemical Characterization Of Compounds 1-3mentioning
confidence: 99%